Laser surface texturing of 316L stainless steel in air and water: A method for increasing hydrophilicity via direct creation of microstructures. (June 2016) - Razi, Sepehr; Madanipour, Khosro; Mollabashi, Mahmoud
Abstract: Laser processing of materials in water contact is sometimes employed for improving the machining, cutting or welding quality. Here, we demonstrate surface patterning of stainless steel grade 316L by nano-second laser processing in air and water. Suitable adjustments of laser parameters offer a variety of surface patterns on the treated targets. Furthermore alterations of different surface features such as surface chemistry and wettability are investigated in various processing circumstances. More than surface morphology, remarkable differences are observed in the surface oxygen content and wettability of the samples treated in air and water at the same laser processing conditions. Mechanisms of the changes are discussed extensively. Highlights: Laser assisted surface patterning of steel by out of focus method is investigated. Water and air are considered as the processing atmospheres. Different surface features alteration in various processing are explored. Mechanisms of the changes in surface characteristics are discussed extensively.